Use of bedaquiline and delamanid in diabetes patients: clinical and pharmacological considerations - Hu MH; Zheng CL; Gao F (Dove Medical Press, 2016)
Minhui Hu,1 Chunlan Zheng,1 Feng Gao2 1Department of Internal Medicine – Section 5, Wuhan Pulmonary Hospital (Wuhan Tuberculosis Control Institute), 2Department of Endocrinology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China Abstract: Antituberculosis (anti-TB) treatment may be affected by both diabetes and hypoglycemic agents in patients with these 2 comorbidities. However, data supporting this conclusion relate only to standard anti-TB therapies. Sirturo® (bedaquiline) and Deltyba® (delamanid), novel drugs for multidrug-resistant tuberculosis (MDR-TB), are recommended for diabetes patients when another effective treatment regimen cannot be provided. Currently, there are no clinical data related to the use of these agents in diabetes patients. Possible alterations in the pharmacokinetics of these novel drugs induced by changes in subcutaneous adipose blood flow, gastric emptying, or nephropathy in diabetes patients, and possible drug–drug interactions with hypoglycemic agents, are of special interest, since the efficacy of bedaquiline and delamanid is concentration dependent. Moreover, it is of fundamental importance to avoid possible additive or synergistic effects of adverse drug reactions in this already vulnerable patient group. We reviewed clinical particularities related to the use of bedaquiline and delamanid in patients with type 1 and 2 diabetes mellitus (DM), as well as pharmacological aspects of the concurrent use of these agents with oral and injectable hypoglycemic agents. Bedaquiline shares liver metabolic pathways with several oral hypoglycemic agents, whereas delamanid may compete with several oral hypoglycemic agents and insulin analogs at protein-binding sites. Special concern exists regarding the use of bedaquiline and delamanid in diabetes patients aged >65 years and patients with severe renal or hepatic impairment or electrolyte disturbances. Concurrent use of bedaquiline and delamanid with insulin analogs, and other hypoglycemic agents that prolong the heart rate-corrected QT interval, such as sulfonylureas and glinides, may enhance this adverse reaction. Hepatic-related adverse reactions may develop more frequently when these drugs are combined with thiazolidinediones and acarbose. Data from Phase III and postmarketing studies are needed to elucidate the effect of DM and hypoglycemic agents on bedaquiline and delamanid effects in MDR-TB patients. Keywords: bedaquiline, delamanid, oral hypoglycemic agents, insulin analogs, pharmacokinetics